Effects of Human, Relational, and Psychological Capitals on New Venture Performance - Wang, Yong; Tsai, Cheng-Hung; Lin, David D.; Enkhbuyant, Oyunjargal; Cai, Juan (Frontiers in Psychology, 2019)
Entrepreneurship research has been focusing on intangible capitals of an entrepreneur or entrepreneurial teams. Intellectual capital has been a useful framework for researching entrepreneurship, though, the inclusion of intangible capital has not been comprehensive enough. We followed and extended this stream to add psychological capital into the discussion of the relationship between intellectual capital and new venture performance. We argue that psychological capital, human capital, and relational capital are representative capitals of entrepreneurs at intra-personal, personal, and interpersonal levels, respectively – none of them can be neglected for new venture success. Based on the analyses of documentary materials of famous entrepreneurs’ interviews from trustable websites/media, this conceptual analyses with case examples found different constructs to serve as important entrepreneurial intellectual capital, which consists of human (i.e., age and education, graduate work experiences, non-graduate work experiences, role models), relational (i.e., trustworthiness and co-founder relations) capitals, and psychological capital (optimism, self-efficacy, Hope, and strength). This study contributes by formalizing psychological capital as a theoretical element of intellectual capital and its effectiveness with other forms of intellectual capital on entrepreneurial performance and growth.